2004
DOI: 10.1111/j.0197-6664.2004.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of remarriage and stepfamily formation for marriage education*

Abstract: Couples in remarriages with stepchildren are a significant portion of the marriage population and have unique educational needs regarding aspects of couple functioning within the context of stepfamily development. From a review of the literature, we examine current curricula focused on these couples. Information is offered on implementation issues regarding recruitment, delivery context, facilitator and participant characteristics, and evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
113
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 36 publications
6
113
0
3
Order By: Relevance
“…Currently, many stepfamily education programs are offered in a variety of ways (Adler-Baeder & Higginbotham, 2004). In their review of evaluated stepfamily education courses, Whitton and colleagues (2008) identified 20 stepfamily education programs implemented between 1978 and 2007.…”
Section: History Of Stepfamily Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, many stepfamily education programs are offered in a variety of ways (Adler-Baeder & Higginbotham, 2004). In their review of evaluated stepfamily education courses, Whitton and colleagues (2008) identified 20 stepfamily education programs implemented between 1978 and 2007.…”
Section: History Of Stepfamily Educationmentioning
confidence: 99%
“…Third, recommendations for stepfamily education evaluation suggest that more research and evaluation be done with low-income participants (Robertson et al, 2006). Fourth, Adler-Baeder and Higginbotham (2004) have reported the need for evaluations with ethnically diverse participants. Finally, Robertson et al (2006) indicated that evaluative research of stepfamily educational courses should follow stepfamily couples for several years to gain insight into the effectiveness of such educational programs.…”
Section: Limitations Of Existing Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many remarriage education programs are designed to serve only couples ). However, some scholars have suggested that formats that serve all family members, including children, have an added benefit (Adler-Baeder and Higginbotham 2004). As the entire family attends, both parents and children can take the skills they have learned in the course and use them in their homes .…”
mentioning
confidence: 99%
“…These stepfamily education programs varied in number of sessions, evaluative measures, and content. Most addressed common stepfamily issues such as co-parenting with an ex-spouse, stepparenting, finances, and communication (Adler-Baeder and Higginbotham 2004). While the majority of these programs were not evaluated for long-term benefits, all showed positive short-term benefits for families involved in stepfamily education.…”
mentioning
confidence: 99%